Warfarinized Patients: Perioperative Mild to Moderate Hemorrhage Undergoing Oral Surgery and Management - A Systematic Review - Nasyam, Fazil Arshad; Jethlia, Ankur; Lunkad, Honey; Kukreja, Pankaj; Ganesh, Rajendran; Haleem, Shaista; Haque, Mainul; Kumar, Santosh (Bangladesh Journal of Medical Science, 2025)
Background The management of patients on warfarin therapy during oral surgical procedures, specifically tooth extractions, has been subject to significant clinical debate. The risk of postoperative bleeding must be balanced against the potential for thromboembolic events upon discontinuation of anticoagulation. This study synthesized findings from various research efforts to elucidate the safety and efficacy of continuing warfarin therapy during dental extractions. Methods A comprehensive literature review examined studies that included patients undergoing tooth extractions while on warfarin therapy. Following the PRISMA guidelines, data were extracted on patient outcomes, particularly the incidence and severity of postoperative bleeding and the use and effectiveness of local hemostatic measures. Results The 6 included papers consistently demonstrated that most patients on warfarin therapy experienced minor bleeding complications postextraction, with severe bleeding events being rare. Local hemostatic measures, including mechanical pressure and pharmacological agents, effectively managed to bleed. The studies varied in terms of hemostatic agents used and pain assessment. Still, the overarching inference pointed towards the safety of continuing warfarin therapy during dental extractions with appropriate local hemostasis. Conclusion Continuing warfarin therapy during dental extractions appears safe for patients with an INR (International Normalized Ratio) maintained within therapeutic ranges. The evidence does not support the necessity for preoperative alteration of warfarin therapy, provided that effective local hemostatic measures are in place. Clinical decisions should be individualized based on patient risk assessments for both bleeding and thromboembolism. BJMS, Volume: 24. Supplementary Issue 2025, Page : 9-23